Changing patterns and mortality of acute myocardial infarction in a coronary care unit. Issue 6064 (26th March 1977) - Hunt, D; Sloman, G; Christie, D; Penington, C
Abstract : Three groups of patients who had been admitted to a coronary care unit with infarction at different periods since 1963 were reviewed to assess whether the outcome in such patients had improved over 12 years. There was a significant reduction in mortality among consecutive patients with mild or severe infarction between 1969-70 and 1974-5. Classifying the patients in all three groups according to their risk factors showed that for each risk factor mortality had decreased since 1963. The incidence of arrhythmias and conduction defects decreased between 1969-70 and 1974-5, and mortality among patients with each arrhythmia also fell. The reduction in mortality may reflect a changing pattern in the natural history of the disease as well as a benefit of improved treatment.